1999
DOI: 10.1046/j.1471-4159.1999.0732569.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin‐Mediated Increases in the Extracellular Levels of β‐Endorphin in the Arcuate Nucleus and Nucleus Accumbens : A Microdialysis Study

Abstract: Although the involvement of both endogenous opioid and serotonergic systems in modulation of pain and emotion was suggested, the neurochemical interaction between these systems in the brain has not previously been studied directly. Herein, the effects of the local application of serotonin (5-HT) and fluoxetine (a 5-HT reuptake inhibitor) on extracellular levels of ␤-endorphin in the arcuate nucleus and nucleus accumbens were assessed in freely moving rats using in vivo microdialysis. The mean basal concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…In the case of nicotine-induced increases in BP, this 'deactivation' of neurotransmission would require that considerable endogenous opioid tone would be present in the denicotinized smoking condition. Although this was not directly investigated in the present report, substantial baseline endogenous opioid tone has been described in the rodent basal ganglia (Zangen et al, 1999) and amygdala (Kraus et al, 1996;Gestreau and Besson, 2000). Consistent with the presence of this tone in human subjects, the opioid receptor antagonist naloxone increased the activity of a number of cortical (eg anterior cingulate, prefrontal and insular, entorhinal and parahippocampal cortices) and subcortical (eg basal ganglia, hippocampus) regions in a recent fMRI study (Borras et al, 2004).…”
Section: Discussionsupporting
confidence: 63%
“…In the case of nicotine-induced increases in BP, this 'deactivation' of neurotransmission would require that considerable endogenous opioid tone would be present in the denicotinized smoking condition. Although this was not directly investigated in the present report, substantial baseline endogenous opioid tone has been described in the rodent basal ganglia (Zangen et al, 1999) and amygdala (Kraus et al, 1996;Gestreau and Besson, 2000). Consistent with the presence of this tone in human subjects, the opioid receptor antagonist naloxone increased the activity of a number of cortical (eg anterior cingulate, prefrontal and insular, entorhinal and parahippocampal cortices) and subcortical (eg basal ganglia, hippocampus) regions in a recent fMRI study (Borras et al, 2004).…”
Section: Discussionsupporting
confidence: 63%
“…It was also shown that 5-HT, either endogenous or exogenously delivered, facilitate the release of b-endorphin in the arcuate nucleus and nucleus accumbens (32). According to the findings of Gemma et al (33), activation of the hypothalamic serotonergic system was produced by central injection of IL-1b.…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, considerable basal ␤-endorphin tone has been directly described in microdialysis studies in some of these regions (arcuate nucleus, nucleus accumbens) (Zangen et al, 1999). Indirectly, through the assessment of increases in glucose metabolism or c-fos expression after low dose naloxone administration, tonic endogenous opioid activity has been described in the brainstem regions and the amygdala of rodents (Kraus et al, 1996;Gestreau and Besson, 2000).…”
Section: Discussionmentioning
confidence: 99%